'I've Never Met A Me': Identity and Philosophy in D'Ailleurs, Derrida. Issue 2 (November 2019) - La Caze, Marguerite
Abstract : The tension between the absence of identity and the feeling of presence theorised in Jacques Derrida's philosophy is revealed in D'ailleurs Derrida, a film bySafaa Fathy (1999) . Fathy's film has had limited scholarly attention, yet it makes a distinctive contribution both to understanding and questioning Derridean thought. I argue that the not-meness of identity is revealed by Fathy through the theme of 'elsewhere' ( ailleurs ) in the film and yet it allows the audience to experience the tone and cadence of Derrida's speaking voice, in counterpoint with contemporary and archival images, thus providing a sense of his philosophy in relation to his life. The film shows how forms of absence such as silence, the not-said, and even pauses are essential to his work. Ultimately the film operates by giving Derrida the location, space, and time to articulate his views on identity, the close relationship between writing and filming, the experience of being 'the Marrano's Marrano, circumcision, forgiveness and hospitality, and absence and presence. Nevertheless, Fathy's film both reflects and questions his philosophical focus on absence and spectrality through a range of cinematic techniques, including reverse shots and cross-cutting between locations.